2001
DOI: 10.1182/blood.v98.10.3035
|View full text |Cite
|
Sign up to set email alerts
|

Splenectomy of rats selectively reduces lymphocyte function-associated antigen 1 and intercellular adhesion molecule 1 expression on B-cell subsets in blood and lymph nodes

Abstract: IntroductionAntigens circulating in the blood are retained in the spleen and presented to a huge number of B and T cells migrating through its different compartments. 1,2 On removal of the spleen the incidence of severe infections increases both in children and adults, 3,4 and there are changes in many immunologic parameters. 5 One lasting change is a high increase in the number of B lymphocytes in the blood, an effect that is constantly observed both in humans 6 and in experimental animals, 7,8 and that compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 46 publications
(49 reference statements)
1
12
0
1
Order By: Relevance
“…[18][19][20] These patients have a high risk of fulminant infection and it is well known that the absence of the spleen leads to several changes in the presence and expression pattern of immune cells in other lymphoid organs. 21 Thus, the spleen plays a central role in the homoeostasis of the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] These patients have a high risk of fulminant infection and it is well known that the absence of the spleen leads to several changes in the presence and expression pattern of immune cells in other lymphoid organs. 21 Thus, the spleen plays a central role in the homoeostasis of the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…A second possibility is that the higher migration rate and lower proliferation rate were responsible. [34] Massive migration of immature B cells into the peripheral circulation has also been described by Ellis et al [32] who reported that the high number of peripheral lymphocytes in their patients indicated a large amount of mature B lymphocytes. This was caused by the increased migration of newly formed B cells from the bone marrow which served as a homeostatic mechanism for the recovery of B cells in the peripheral circulation due to castration.…”
Section: Discussionmentioning
confidence: 57%
“…This result is also supported by the persistence of T cells and memory B cells that already exist in the lymphoid organs and an increase in Kupffer cell activity, indicating that the rate of proliferation was not affected. [38] Milićević et al [34] found that the migration and proliferation of B cells was influenced by surface molecules such as lymphocyte function-associated antigen 1 (LFA-1), intercellular adhesion molecule 1 (ICAM-1), L-selectin, 4-integrins, the IL-2-R chain, CD44, and MHC class II, which affects the initial attachment of B cells in the endothelium and their infiltration into the tissue. Removing the spleen caused a decrease in the expression of LFA-1 and ICAM-1 in B cells, which would support the acceleration of B cell migration to the peripheral organs and increase in blood circulation.…”
Section: Discussionmentioning
confidence: 99%
“…It is not known whether they also contain sessile T-cell populations. During migration through lymphoid tissues, which lasts approximately 24 hours (Westermann et al, 2001a), T and B cells temporarily either up-or down-regulate the expression of adhesion molecules (Luettig et al, 2001;Milicevic et al, 2001), and they absorb surface molecules from other cell types (Flugel et al, 2001;Hwang et al, 2000). These changes are reversed before leaving the tissue.…”
Section: Sourcementioning
confidence: 99%